Taudhifu Muhtawa Instagram @gramatika_arab fii Ta’līm an-Nahwi al-Arabiy : Tahlīl Muhtawā Nau'ī Qāim 'ala al-Wasāith as-Sam'iyyah al-Bashariyyah : Utilizing Instagram Content ‎@gramatika_arab in Teaching Arabic Grammar: A Qualitative Content Analysis Based on Audiovisual Media - M. Nurul Huda (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2025)
Instagram is one of the social media completed with various features and used as a medium for information and communication. One of its functions is to make it easier for Arabic learners to access Instagram accounts that provide several audio-visual-based Arabic content. This study aims to analyze the implementation and effectiveness of audiovisual media-based learning innovations through the application of Instagram @gramatika_arab in developing Arabic language learning skills. This research is a qualitative content analysis with Instagram @gramatika_arab as the subject. Data sources in this study consist of primary data sourced from Instagram @gramatika_arab and secondary data in the form of several scientific journals relevant to this study. The data collection method applied is the documentation method. Data analysis is carried out during the research. The results showed that Instagram @gramatika_arab became one of the accounts providing an audiovisual based on Arabic content that is widely accessed by Arabic language learners, especially students of MAN 1 Serang. It is even accessed by several other countries such as Malaysia, Thailand, and Morocco. Content in the form of Arabic quizzes, pamphlets, and handwriting can attract and facilitate Arabic learners in understanding the material. In addition, Arabic language learners can easily access these contents whenever and wherever. Keywords: Arabic, Audio Visual, gramatika_arab, Instagram